Damage detection in steel plates using discrete cosine transformation techniques and artificial neural network - Paulraj, M.P.; Mohd Shukry, Abdul Majid; Sazali, Yaacob; Mohd Hafiz, Fazalul Rahiman; R Pranesh, Krishnan (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.